Arham in the Qur'an, Surah Ar-Ra'd, Ayah 8, and Its Implementation in Medical Instrumentation - Fadhilah, Umi; Azizah, Alfiyatul (Universitas Muhammadiyah Surakarta, 2023)
This study aims to examine the concept of arham in the Qur'an, especially in Surah Al-Ra'd verse 8, and analyze its implementation in medical instrumentation through qualitative methods based on literature or library research. This study uses a text analysis approach to the Qur'an to understand the meaning and implications of arham in the context of the identified verses. Furthermore, through a literature review and library research, this study explores information related to implementing the concept of arham in developing medical technology and instrumentation. The results of this study are expected to provide insight into how the values of arham contained in the teachings of the Qur'an can be integrated and implemented in the development of medical instruments. In addition, this study can contribute to further understanding the relationship between religious principles and scientific progress in the health sector. The practical implications of this study can help medical practitioners, researchers, and policymakers to design and develop medical technology that is more humanistic and by the religious values contained in the Qur'an.